Significant correlation between anti-müllerian hormone and embryo euploidy in a subpopulation of infertile patients. Issue 5 (November 2017) - Gat, Itai; AlKudmani, Basheer; Wong, Karen; Zohni, Khaled; Weizman, Noga Fuchs; Librach, Clifford; Sharma, Prati
Abstract: Anti-Müllerian hormone (AMH) is a standard marker of ovarian reserve. Correlation between AMH and egg euploidy is controversial. We evaluated the association between AMH and blastocyst euploidy rate examined by pre-implantation genetic screening (PGS). This retrospective study was conducted at the CReATe Fertility Centre. We included single IVF cycles of 216 infertile couples, which resulted in 911 blastocysts subjected to array comparative genomic hybridization and evaluated IVF outcome after embryo transfer. The average age and median AMH of female patients were 37.2 (SD = 3.8) and 20 pmol/l, respectively, and the average euploidy rate was 38.3%. Using multivariate regression controlling for age, antral follicle count, body mass index and parity, there was a significant association between serum AMH and proportion of euploid embryos ( P = 0.02), due to the dominant ≤36 age group in which significant correlation between AMH and euploidy rate ( P = 0.02) was demonstrated. Clinical outcome was similar, including biochemical, clinical and ongoing pregnancy rates as well as pregnancy loss. This study shows a correlation between AMH and aneuploidy rate, specifically among infertile patients younger than 37 years old. Study limitations are discussed.